Kajian Geoekonomi Kerja Sama Alih Teknologi Sektor Pelabuhan Antara Indonesia dan Singapura - Muhammad Naufal Musri (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2022)
This research describes the geoeconomic partnership built between Indonesia and Singapore. The discussion focuses on Indonesia and Singapore’s cooperation in the field of port development sector and technology transfer. In preparing this paper, the author employed a descriptive analytic research method to explore this issue. Data were gathered from a variety of literatures from different research sources, including publications and agreement documents from official, books, and scientific articles connected to the current cooperation. The cooperation between Indonesia and Singapore, which is highlighted in this publication, should focus more on the port industry, which is one of the key areas for boosting the economies of the two nations. According to an economic analysis of the port technology transfer issue, collaboration between Singapore and Indonesia is undoubtedly quite likely. It should be noted, however, that Singapore's position of managing technology independently as a necessity for sovereignty serves as a caution to Indonesia to always have a backup plan with other parties.